TIME DEPENDENT FEATURES IN TREMOR SPECTRA - Powell T.W.; Neuberg J. (My University, 2003)
Harmonic spectral peaks are observed in the tremor spectra of many different volcanoes, and in some cases these spectral lines have been seen to change with time. This has also been observed for the tremor at the Soufriere Hills volcano on Montserrat, West Indies, where the spectral lines are sometimes seen to glide apart before an explosion. We propose a model of repeated triggering of low-frequency earthquakes to explain these gliding lines using the relationship δt=1/δν, where δt and δν are time and frequency spacing, respectively, and investigate factors which can affect the observation of these spectral peaks. Noise and amplitude variation are shown to have little effect on the spectral peaks; however the time gap between events must be nearly constant over several events. An error with a standard deviation of 2% or less is required for the spectral lines to be observed in the frequency range 0.5-10 Hz. We can reproduce the gliding spectral lines from a specific tremor episode preceding an explosion by changing δt from 1 to 0.31 s over a time period of 12 min. Using this relationship and an Automated Event Classification Analysis Program (AECAP), we can monitor δt over a long time period. The AECAP also extracts other seismic parameters such as energy, duration and spectral characteristics. An initial comparison between low-frequency seismic energy and cyclic tilt shows a correlation between the two, but this does not hold for later cycles.
Keywords: HARMONIC SPECTRAL LINES; VOLCANIC TREMOR; GLIDING; LOW-FREQUENCY EARTHQUAKES; MONTSERRAT; SWARMS